2019
DOI: 10.1111/imj.14439
|View full text |Cite
|
Sign up to set email alerts
|

Cost of screening for lung cancer in Australia

Abstract: Background Lung cancer screening can reduce lung cancer mortality. Australian cost estimates are important to inform policy but remain uncertain. Aim To describe the first direct medical costs associated with lung cancer screening in Australia. Methods Single‐centre prospective screening cohort. Healthy volunteers (age 60–74 years, current or former smokers quit <15 years prior to enrolment, ≥30 pack‐years exposure) underwent baseline and two annual incidence computed tomography (CT) screening scans. Health st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…The number of LC cases was estimated from the number of LC deaths by applying 5-year survival. 5-year survival Cost of LDCT scan Australian MBS fee $302 Average cost of follow-up CT QLCSS [ 26 ] $476 Cost false positive QLCSS [ 26 ]. Non-CT work-up $861.8 Costs of LC management by stage Health-system costs based on the 45 and up study [ 25 ] (inclusive of pre-diagnosis costs) Stage I: $62,327; Stage II: $69,235; Stage III: $63,436; Stage IV: $56,701; Stage “unknown”: $38,388 Cost pre-diagnosis Health-system costs based on the 45 and up study [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The number of LC cases was estimated from the number of LC deaths by applying 5-year survival. 5-year survival Cost of LDCT scan Australian MBS fee $302 Average cost of follow-up CT QLCSS [ 26 ] $476 Cost false positive QLCSS [ 26 ]. Non-CT work-up $861.8 Costs of LC management by stage Health-system costs based on the 45 and up study [ 25 ] (inclusive of pre-diagnosis costs) Stage I: $62,327; Stage II: $69,235; Stage III: $63,436; Stage IV: $56,701; Stage “unknown”: $38,388 Cost pre-diagnosis Health-system costs based on the 45 and up study [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…8 In Australia, it has been shown that that high-quality LDCT screening is feasible and that long-term smoking cessation in a CT screening population is effective; the costs of screening and associated impacts on quality of life have also been reported. [9][10][11] The International Lung Screen Trial is currently underway within Australia to assess the benefits of risk prediction models for patient selection to improve the efficiency of CT screening. A 2013 Australian survey of 90 patients at risk of lung cancer found the majority would be willing to participate in screening with LDCT.…”
Section: Screeningmentioning
confidence: 99%
“…This eligibility window may widen further still in light of the recent studies demonstrating the efficacy of acute intervention in selected patients at times longer than 6 h after symptom onset. [16][17][18] Despite the increase in stroke calls, there were also significantly fewer patients who received thrombolysis following the protocol change. Interestingly, more patients in the post-intervention group were ineligible for thrombolysis due to the presence of contraindications.…”
Section: Helsinki Model In Westmeadmentioning
confidence: 99%